HUBUNGAN ANTARA KONSEP DIRI DAN KECEMASAN BERBICARA DI DEPAN KELAS PADA MAHASISWA UNIVERSITAS ESA UNGGUL JAKARTA YANG AKTIF DI SEMESTER GANJIL 2015/2016 - Violla, Violla; Sitasari, Novendawati Wahyu (Jurnal Psikologi : Media Ilmiah Psikologi, 2016)
AbstractUniversity students expected to develop intellectual and personality skill, especially in verbal skill. One of tasks to improve verbal skill is presentation task. But, there are still students experience in speaking anxiety in front of class despite of verbal communication skill will be required for job acquirements. This anxiety among students suspected was affected by self-concept. The purpose of this research is to determine correlation between self-concept and speaking anxiety in front of class among students of Esa Unggul University Jakarta. This research used non-experimental correlational method with probability sampling technique and proportionate stratified random sampling. The sample consisted of 180 active regular students of Esa Unggul University Jakarta class of 2012-2014 academic year 2015/2016. Self-concept scale modified from Tennessee Self-Concept Scale (TSCS) devised by W. H. Fitts and yielded reliability value (rxx)=0,945 whereas speaking anxiety in front of class scale in order of Lang’s public speaking anxiety responses theory and yielded reliability value (rxx)=0,949. Based on data analysis of Pearson Product Moment correlation coefficients were found r=-0,353 and significant 0,000 level (p <0,05). It means, hyphotesis in this research was accepted, there is negative correlation between self-concept and speaking anxiety in front of class among students of Esa Unggul University. Keywords: self-concept, speaking anxiety in front of class, students AbstrakMahasiswa diharapkan dapat mengembangkan kemampuan intelektual dan kepribadian, khususnya kemampuan verbal. Salah satu tugas untuk mengembangkan kemampuan verbal adalah tugas presentasi. Namun masih ada mahasiswa yang mengalami kecemasan tinggi saat berbicara di depan kelas, padahal keterampilan berbicara secara lisan dibutuhkan di dunia kerja. Kecemasan yang dialami mahasiswa ini diduga dipengaruhi oleh konsep diri. Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dan kecemasan berbicara di depan kelas pada mahasiswa. Penelitian menggunakan metode korelasional non-eksperimental dengan teknik pengambilan sampel probability sampling berjenis proportionate stratified random sampling. Sampel dalam penelitian adalah 180 mahasiswa reguler aktif Universitas Esa Unggul Jakarta angkatan 2012-2014 tahun ajaran 2015/2016. Skala konsep diri yang digunakan dimodifikasi dari Tennessee Self-Concept Scale (TSCS) milik W. H. Fitts dengan reliabilitas (rxx)=0,945. Sedangkan skala kecemasan berbicara di depan kelas disusun berdasarkan teori respons kecemasan berbicara di depan umum milik Lang dengan reliabilitas sebesar (rxx)=0,949. Berdasarkan analisis data dengan teknik korelasi Pearson Product Moment diperoleh nilai koefisian korelasi r=-0,353 dengan taraf signifikansi 0,000 (p<0,05). Artinya, hipotesis dalam penelitian ini diterima yaitu ada hubungan negatif antara konsep diri dan kecemasan berbicara di depan kelas pada mahasiswa Universitas Esa Unggul Jakarta. Kata kunci: konsep diri, kecemasan berbicara di depan kelas, mahasiswa